Carotenoids synthesis affects the salt tolerance mechanism of Rhodopseudomonas palustris - Li, Meijie; Zhu, Tongtong; Yang, Rumeng; Wang, Zhaobao; Liu, Min; Yang, Jianming (Frontiers in Microbiology, 2023)
Rhodopseudomonas palustris CGA009 is a gram-negative, purple non-sulfur, metabolically diverse bacterium with wide-ranging habitats. The extraordinary ability of R. palustris to decompose a variety of raw materials and convert them into high-value products makes it an attractive host for biotechnology and industrial applications. However, being a freshwater bacterium R. palustris has limited application in highly-saline environments. Therefore, it is of great significance to obtain the salt-tolerant strain of R. palustris and understand its tolerance mechanism. In this study, R. palustris CGA009 was successfully evolved into eight salt-tolerant strains using an adaptive laboratory evolution technique. RPAS-11 (R. palustris anti-salt strain 11) was selected as the best salt-tolerant strain and was used in further studies to explore the salt-tolerance mechanism. The expression of most genes associated with the carotenoid synthesis in RPAS-11 increased significantly under high concentration of salt stress, suggesting that carotenoid synthesis is one of the reasons for the salt tolerance of RPAS-11. Gene overexpression and knockout experiments were performed to get clear about the role of carotenoids in salt stress tolerance. RPAS-11-IDI, the mutant with overexpression of IDI (Isopentenyl diphosphate isomerase) exhibited enhanced salt tolerance, whereas the knockout mutant CGA009-∆crtI showed a decline in salt tolerance. In addition, the results indicated that rhodopin, a carotenoid compound, was the key pigment responsible for the salt tolerance in R. palustris. Furthermore, the production of lycopene, a widely-used carotenoid, was also increased. Taken together, our research helps to deepen the understanding of the salt tolerance mechanism of R. palustris and also widens the application of R. palustris in highly-saline environments.